A Diversitas Adaptasi Pergerakan pada Kingdom Animalia: Analisis Kompleksitas Sistem Motorik dari Hewan Sederhana hingga Kompleks - Viga, Nindya; Wibowo, Alif Prasetyo; Simamora, Agnes Monika; Manalu, Enjel Febriani; Lubis, Fatiha Salsabila; Manik, Julika Indriani (Jurnal Sains Indonesia, 2024)
Abstract: This study explores the diversity of movement adaptations within the Animal Kingdom, from simple to complex organisms, with a focus on the motor system's complexity in response to environmental changes. Understanding this diversity is crucial due to its significant impact on global ecosystems, particularly regarding urbanization, deforestation, and climate change. Some species exhibit unique movement patterns, like large-scale migrations, that play a vital role in ecosystem stability. This research uses literature synthesis and descriptive qualitative analysis, revealing movement strategies influenced by ecological and behavioral factors. The study highlights the importance of protecting migration routes for biodiversity conservation efforts.